(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Packed red blood cells (PRBCs) represent the most frequently transfused blood component worldwide. During storage, PRBCs undergo progressive biochemical and morphological alterations collectively termed the "storage lesion," which may compromise transfusion efficacy and patient outcomes. Pre-analytical variables including collection techniques and processing times further influence product quality. Methods: This prospective observational study analyzed 120 PRBC units collected from voluntary blood donors. Pre-analytical variables including ambient temperature exposure and processing time were documented. Hematological parameters including hemoglobin, hematocrit, mean corpuscular volume (MCV), red blood cell count, potassium levels, pH, lactate concentrations, and percentage hemolysis were measured at days 0, 7, 14, 21, 28, and 35 of storage. Results: Significant progressive changes were observed throughout the storage period. Hemoglobin decreased from 18.42 ± 1.28 g/dL to 17.15 ± 1.34 g/dL (p<0.001). Supernatant potassium increased substantially from 4.82 ± 0.76 mEq/L to 48.56 ± 6.42 mEq/L (p<0.001). Percentage hemolysis rose from 0.12 ± 0.04% to 0.68 ± 0.18% (p<0.001). pH declined from 7.08 ± 0.06 to 6.52 ± 0.12 (p<0.001). Units with prolonged pre-analytical processing time (>8 hours) demonstrated significantly higher hemolysis rates (0.82 ± 0.21% vs. 0.54 ± 0.14%, p<0.01) at day 35. Conclusion: PRBCs undergo significant storage-related hematological deterioration, with marked changes observed particularly after day 21. Pre-analytical variables substantially influence final product quality, emphasizing the importance of standardized processing protocols in blood banking operations.